Comparative analysis of cross-saturation phenomenon in the synchronous reluctance machine of a 6 and 3‑phase winding - Mysiński, Michał (Archives of Electrical Engineering, 2026)
The paper deals with research on the direct and quadrature axis cross saturation effect in the synchronous reluctance machine (SynRM). The comparative analysis between the performance of the 4-pole SynRM of 3-phase and 6-phase windings have been conducted exploiting developed 2D finite element models. In the numerical models of the studied machines, the locked rotor method was adopted in which the direct (d ) and quadrature (q) axis currents iq and id were forced to determine magnetic fluxes in the d-q axes, respectively. Next, determined magnetic flux maps have been used to determine a simple analytical model taking into account the cross-saturation effect. The quality of the proposed analytical description of the cross-saturation phenomenon has been evaluated by comparison to the results of simulations in order to assess the possibility of adapting this description in the control algorithms of SynRM drives.